Comparative Transcriptome Analyses Reveal a Transcriptional Landscape of Human Silicosis Lungs and Provide Potential Strategies for Silicosis Treatment - Pang, Junling; Luo, Ya; Wei, Dong; Cao, Zhujie; Qi, Xianmei; Song, Meiyue; Liu, Ying; Li, Zhaoguo; Zhang, Jin; Li, Baicun; Chen, Jingyu; Wang, Jing; et al. (Frontiers in Genetics, 2021)
Silicosis is a fatal occupational lung disease which currently has no effective clinical cure. Recent studies examining the underlying mechanism of silicosis have primarily examined experimental models, which may not perfectly reflect the nature of human silicosis progression. A comprehensive profiling of the molecular changes in human silicosis lungs is urgently needed. Here, we conducted RNA sequencing (RNA-seq) on the lung tissues of 10 silicosis patients and 7 non-diseased donors. A total of 2,605 differentially expressed genes (DEGs) and critical pathway changes were identified in human silicosis lungs. Further, the DEGs in silicosis were compared with those in idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary diseases (COPD), to extend current knowledge about the disease mechanisms and develop potential drugs. This analysis revealed both common and specific regulations in silicosis, along with several critical genes (e.g. MUC5AC and FGF10), which are potential drug targets for silicosis treatment. Drugs including Plerixafor and Retinoic acid were predicted as potential candidates in treating silicosis. Overall, this study provides the first transcriptomic fingerprint of human silicosis lungs. The comparative transcriptome analyses comprehensively characterize pathological regulations resulting from silicosis, and provide valuable cues for silicosis treatment.